2021
DOI: 10.1016/j.amsu.2021.102496
|View full text |Cite
|
Sign up to set email alerts
|

Double-tract reconstruction for oesofagocardial gastric cancer: A systematic review

Abstract: The number of people with gastric cardia and distal oesophageal cancers has increased in the last five years. The surgical treatment method of choice is proximal gastrectomy, with an option being reconstruction of the gastrointestinal tract. There are many reconstruction techniques for anastomosis of the oesophagus and distal parts of the digestive tract. However, all can result in complications. This systematic review aims to identify the efficacy of the double-tract reconstruction method after gastric resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…One study showed that DTR could better prevent reflux esophagitis and improve quality of life for patients who underwent radical PG, and GR had a linear relationship with the global health status score [ 14 ]. A systematic review found that DTR, which is a promising surgical method for patients with oesofagocardial gastric cancer, was associated with few complications related to GR disease and dysphagia [ 20 ]. Furthermore, a network meta-analysis indicated that compared with other surgical methods, PG-DTR can significantly reduce the incidence of postoperative reflux esophagitis and anastomotic stenosis by searching for articles published between January 1, 1990, and February 1, 2021 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that DTR could better prevent reflux esophagitis and improve quality of life for patients who underwent radical PG, and GR had a linear relationship with the global health status score [ 14 ]. A systematic review found that DTR, which is a promising surgical method for patients with oesofagocardial gastric cancer, was associated with few complications related to GR disease and dysphagia [ 20 ]. Furthermore, a network meta-analysis indicated that compared with other surgical methods, PG-DTR can significantly reduce the incidence of postoperative reflux esophagitis and anastomotic stenosis by searching for articles published between January 1, 1990, and February 1, 2021 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is the fourth most common malignant tumor worldwide and is one of the leading causes of cancer-related death[ 1 ]. Surgical resection of the entire tumor and complete lymph node dissection are the main treatments for gastric cancer[ 2 ].…”
Section: Introductionmentioning
confidence: 99%